Differental diagnosis of painless lymphadenopathy: challenges in everyday clinical practice with case report and literature overview - Marković, Marija; Miljković, Ana (General Practice, 2025)
Introduction. Lymphadenopathy is defined as an abnormal finding during a physical examination, indicating that the lymph nodes are abnormal in size, consistency, and number. A thorough personal history and detailed physical examination allow the physician to formulate an appropriate diagnostic strategy. It is important to approach differential diagnoses with caution, as there is a wide range of potential causes and often nonspecific clinical presentations. Painless lymphadenopathy, in particular, presents a significant clinical challenge, especially in primary healthcare settings. Case report 1. A 54-year-old female patient presented with a lump that she had noticed in her left groin. A detailed physical examination revealed a painless lump measuring 25 mm in diameter. An ultrasound of the groin showed an enlarged lymph node with peripheral vascularization. A biopsy of the lymph node confirmed the presence of metastatic cervical carcinoma. A PET-CT scan indicated a solitary lump along the upper uterine margin, along with liver metastases. The oncology team recommended three weeks of chemotherapy. The patient has since undergone six cycles of chemotherapy. Case report 2. A 76-year-old male patient presented with a lump in his right armpit that had been present for several months, but he reported no other symptoms. A physical examination revealed a lump the size of an apple located under the right armpit, which was painless to the touch. A biopsy confirmed that it was a metastatic melanoma. An abdominal ultrasound showed the presence of liver metastases. A dermatological examination revealed a suspicious skin tumor in the lumbar area, measuring 1 cm in diameter, also highly suggestive of melanoma. After excising the lesion, the pathological findings confirmed the diagnosis. Conclusion. Painless lymphadenopathy is a common finding that presents diagnostic challenges, with a broad range of causes that can vary from benign to malignant. Timely recognition and appropriate interventions are crucial for treatment outcomes.